Hydrologic remobilisation of tephra‐fall deposits: A sedimentological analysis throughout fluvio‐lacustrine systems of North‐West Patagonia - Losano, Nahuel Ezequiel (2024)
This paper explores the response to Holocene ash inundation in different sub-environments of two fluvio-lacustrine systems, Las Piedritas and Totoral, focussing on the processes of volcaniclastic remobilisation. Sediment cores and outcrops were used to recognise three deposit types, noting how some differ from lahars, through sedimentological and stratigraphic analysis: (1) thick, laterally discontinuous, pumice-dominated deposits occur overlying alluvial plain and lower terrace surfaces across both watersheds; (2) chaotic, extremely poorly sorted and matrix-supported beds composed of both epiclastic and pyroclastic material occur as two conspicuous deposits at Las Piedritas outcrops, in a low-gradient confined channel setting; and (3) layers with an exclusively pyroclastic composition and no flow sedimentary structures or fragment roundness were found draping each of the two chaotic intervals and intercalating with the background sediment in Las Piedritas prodelta. Thick pumice packages capping the floodplains resulted from the overflow of streams carrying a floating pumice load. Due to its positive buoyancy, the pumice is transported as a slowly moving overlying mantle without mixing with the streamflow. The disorganised pattern and poor sorting of the matrix-rich polymictic beds are consistent with laminar, gravity-driven, high-concentration flows. They constitute secondary lahars, originating upstream from large run-off processes that reworked a pyroclastic substrate. The lack of reworking features in the vitric-rich units identified in the lake core retrieved from Las Piedritas prodelta, as well as the continuous and widespread occurrences of those interbedded in upstream outcrops, indicate an airfall origin. No reworked tephra unit is recognised in the prodelta sediment record, although various deposits from the hydrologic remobilisation of airfall tephra are found along the subaerial portion of both watersheds. Apparently, large amounts of flotation-remobilised tephra were retained on the delta plain, while another considerable fraction would have been carried away from the creek mouth under the influence of dominant regional winds.